The Implementation of Empiricism in the Vocabulary Drilling Method in Arabic Language Learning at Bina Taruna High School in Surabaya: Implementasi Empirisme Terhadap Praktik Metode Drilling Kosakata Dalam Pembelajaran Bahasa Arab Di SMA Bina Taruna Surabaya - Alauddin, Ilham; Nurdin, Nur Indah; Aqilah, Nur; Yusuf, Kamal (Madrosatuna: Journal of Islamic Elementary School, 2025)
Empiricism is a technique or approach that emphasizes experience, especially through the senses or sensory experiences that aim to form skills in memorizing and pronouncing Arabic vocabulary automatically through consistent repetition. In repetition through practice (direct experience) can also aim to strengthen memory and form habits. In the context of drilling, continuous repetition of vocabulary helps to create strong associations between sound, meaning, and writing, which is a form of reinforcement in learning. This drilling method is applied to practice the pronunciation of Arabic vocabulary so that it can help achieve good oral and written skills. For example, repeating new words until you get used to hearing and saying them. Implementation of the approach using the drilling method in vocabulary learning is very influential for pronunciation and memorization of Arabic words systematically so that it can form and strengthen the correct pronunciation response. This research is a descriptive qualitative research using data collection techniques through observation, interviews and documentation and data analysis with an interactive model, namely data collection, data reduction, data presentation and drawing conclusions, as well as using data validity in the form of triangulation. The expected results of this method indicate that the implementation of empiricism using the drilling method for Arabic vocabulary pronunciation and memorization has improved. This is evident in the increase in Arabic vocabulary during Arabic language learning. However, using the drilling method also has advantages and disadvantages. Among the advantages of using the drilling method are that it makes it easier for students to pronounce and memorize vocabulary, makes it easier to remember, and fosters student enthusiasm. Disadvantages include stress due to weak memorization and boredom due to repeated vocabulary.